The Trolling Verbal Noun and its literary sites in the Arabic language - Abdul Razak, Solahuddin Mansur; Dollah, Nafi @ Hanafi (IIUM Press, 2017)

(untitled)
Research Summary Understanding the issues of the Arabic language and its secrets makes us undoubtedly aware of the flexibility of the Arabic language and its idioms. This is what this research touches upon. It deals with: the concept of the The Trolling Verbal Noun and its literary sites in the Arabic language in the Arabic language; the difference between it and its explicit and implicit types, its names; Through an analytical descriptive approach that shows the impact of thought on the Arabic language in general, and on the identification of the trolling verbal name in particular.